A New Power System Restoration Technique based on WAMS Partitioning - Phanendra Babu, N. V.; Suresh Babu, P.; Siva Sarma, D. V. S. S. (Engineering, Technology & Applied Science Research, 2017)
An important feature of a Wide-Area Measurement System (WAMS) is the ability to recover data during a communication failure. This paper presents a novel scheme of partitioning a PMU installed power network into a number of WAMS regions in order to make the power system restoration process simpler. This algorithm also proposes the optimal placement of Phasor Data Concentrators (PDCs) in each region to record the data from PMUs. This paper considers the restoration constraints like transformer equivalent bus, generation-load balance and the observability of region for the partitioning of power system. The proposed scheme is demonstrated with an IEEE-30 bus system. It is then applied on IEEE-39, IEEE-118 bus systems and on a Northern Regional Grid of the Indian Power Grid.